PEMBAGIAN SEMBAKO DAN PENDAMPINGAN TRAUMA HEALING PEN PASCA BENCANA BANJIR DAN TANAH LONGSOR DI MANADO - Lawodi, Yulisnawati; Lamusu, Rahman; Abulebu, Henny Indriyani; Bansambua, Elce Misba; Pakpahan, Irnovia B.; Bangguna, David S.V.L (Jurnal Abdi Insani, 2025)
Flash floods in the city of Manado hit Singkilernate Tanjung District, Mapanget District, Tikala District, Tuminting District, Wenang District, Sario District, Bunaken District, Paal Dua District, Wanea Singkil District. Meanwhile, landslides hit Paal Dua District, Tikala District, Singkil District, Wanea District, Bunaken District, Mapanget District and Wenang District. The flood and landslide disaster claimed 6 lives, resulted in 219 houses being heavily damaged, 166 moderately damaged, 761 lightly damaged, several public facilities such as schools, churches, mosques and sub-district offices being flooded and causing ± 279 families/1,925 people to flee to the nearest village. Based on the flood conditions in the city of Manado, the PKM Team from the Faculty of Engineering, Sintuwu Maroso University carried out community service activities after the flash flood and landslide disaster in Manado. From the results of the PKM Team's activities after the flood and landslide in Manado, it can be concluded that the people in the 3 sub-districts visited for the PKM activities were very enthusiastic and grateful, especially for the trauma healing activities, because these activities were very helpful and motivating for the children at the location. Refugees are entertained and do not get lost in post-disaster sadness. Apart from that, the Manado City government hopes that similar activities will be carried out in other refugee camps to alleviate trauma in children.